PENERAPAN MODEL VISUAL, AUDITORY, KINESTHETIC (VAK) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Dinita, Sonia; Aprinawati, Iis; Fadhilaturrahmi, Fadhilaturrahmi; Nurhaswinda, Nurhaswinda; Marta, Rusdial (Jurnal Dedikasi Pendidikan, 2024)
This study investigated the effectiveness of the Visual, Auditory, Kinesthetic (VAK) model in improving the initial reading skills of grade 1 students at SDN 007 Bangkinang Kota. The research was motivated by the low reading ability observed in this group of students. Employing a class action research (PTK) design with two cycles, the study involved 26 students (13 male and 13 female). Each cycle consisted of two meetings and four stages: planning, implementation, observation, and reflection. Data collection, conducted in July 2023, utilized documentation and observation techniques, analyzed qualitatively and quantitatively. Instruments included teacher and student activity observation sheets, and student worksheets. Pre-action results revealed a learning completeness rate of only 30.76%. Following the implementation of the VAK model, this rate progressively increased across both cycles. By the end of cycle II, meeting II, the learning completeness rate reached 92.30%, with 24 students achieving mastery. These findings suggest that the VAK model holds significant potential for enhancing initial reading abilities in grade 1 students